Computer simulation of a Rietema-family hydrocyclone used in irrigated agriculture - Tonin, Paulo (2014)
The hydrocyclone is a centrifugal separator that has been used for over 50 years in the chemical processing and mining industries. In irrigated agriculture in Brazil it is not used as often. One reason for this is the poor understanding by designers of the complex phenomena involved in the internal flow of the hydrocyclone, and the lack of knowledge of new computational tools available on the market. This study evaluates the use of Computational Fluid Dynamics (CFD) as a potential tool to be used in the design and optimisation of hydrocyclones used in irrigated agriculture. A 50 mm Rietema-family hydrocyclone is simulated using CFD. The turbulent flow inside the hydrocyclone is modelled using the Reynolds Stress Model, and a Eulerian approach is employed to model the multiphase flow. Numeric validation is performed by comparing the results of the simulation with data found in the literature. The global mass balance observed for both the single-phase and multiphase flows shows good agreement of the obtained results with data in the literature. Furthermore, the static pressure field, the axial and tangential velocity and the volume fraction of sediments in the hydrocyclone are obtained. The article shows that CFD is a useful tool in explaining the process of sediment separation in the hydrocyclone, and can therefore be used in the design and optimisation of such equipment.